Impact-ionization-assisted intermediate band solar cell. - Luque, A. (IEEE Transactions on electron devices)
The effect on the efficiency of the intermediate band solar cell of certain types of impact ionization mechanisms is studied. It turns out to have several interesting advantages. For example, this mechanism may lead to cells with an efficiency that, although similar to that of the multijunction cells, would be otherwise very insensitive to the spectral mismatch. The efficiency of structures of p, n, or intrinsic type is also discussed in addition to the metallic intermediate band analyzed in earlier works.